1982
DOI: 10.1111/j.1365-2125.1982.tb02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood quinidine levels and cardiac effects in white British and Nigerian subjects.

Abstract: 1 Differences between whites and blacks have been described in the incidence and patterns of cardiac disease and in electrocardiographic features. 2 The objective of the present study was to see if the ECG response to the same plasma and red blood cell quinidine concentration differed between whites and blacks. 3 It was found that following a standard single oral dose of quinidine both plasma and red blood cell quinidine concentrations tended to be lower in seven healthy white British subjects than in seven he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…this is subsequently transferred to the simulation and results in a large difference between the free and total concentration scenarios. Similar effects can be observed for the Olatunde study (Olatunde and Price Evans, 1982), where the concentrations are comparable to those in the work of el-eraky. there is a difference of up to 30 ms in the ΔQTc between free and total scenarios, although it this connected with an underprediction of the plasma concentration in the Olatunde study, which aligns and mitigates the PD effect and makes it less spectacular.…”
Section: Results Presented Insupporting
confidence: 85%
See 1 more Smart Citation
“…this is subsequently transferred to the simulation and results in a large difference between the free and total concentration scenarios. Similar effects can be observed for the Olatunde study (Olatunde and Price Evans, 1982), where the concentrations are comparable to those in the work of el-eraky. there is a difference of up to 30 ms in the ΔQTc between free and total scenarios, although it this connected with an underprediction of the plasma concentration in the Olatunde study, which aligns and mitigates the PD effect and makes it less spectacular.…”
Section: Results Presented Insupporting
confidence: 85%
“…the study inclusion criteria were: a) healthy Caucasian volunteers, b) availability of information about the quinidine pharmacokinetics, ideally presented as a drug plasma concentration change in time, c) PD results presented as Qt/ QTc or ΔQT/ΔQTc (regardless of the correction type), thus comparable with the simulation outputs. Nine papers fulfilling such conditions were identified and used for the study (Belz et al, 1982;Ching et al, 1991;El-Eraky and Thomas, 2003;Fieldman et al, 1977;Kaukonen et al, 1997;laganiere et al, 1996;Min et al, 1996;Olatunde and Price Evans, 1982;Shin et al, 2007). Characteristics of the clinical studies derived from the identified papers are presented in Table 1.…”
Section: Datamentioning
confidence: 99%
“…There are relatively few data on interethnic differences in drug‐induced QT prolongation. Olatunde & Price Evans examined the relationship between serum quinidine concentrations and cardiac effects in white British and Nigerian subjects [17]. They reported that quinidine concentrations in white British subjects tended to be lower than those in Nigerians, yet the quinidine‐induced QTc increase was greater in white British subjects than in Nigerians.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively few data on interethnic differences in druginduced QT prolongation (Olatunde and Price Evans 1982;Shin et al 2006). It is reported that quinidine concentrations in white British subjects tended to be lower than those in Nigerians, yet the quinidine-induced QTc increase was greater in white British subjects than in Nigerians (Olatunde and Price Evans 1982). Also, it is suggested that Korean subjects are less sensitive to quinidine-induced QTc prolongation than Caucasian subjects (Shin et al 2006).…”
Section: Resultsmentioning
confidence: 95%
“…These determinants might lead to differences in the basic pattern and/or drug-induced QTc changes. There are relatively few data on interethnic differences in druginduced QT prolongation (Olatunde and Price Evans 1982;Shin et al 2006). It is reported that quinidine concentrations in white British subjects tended to be lower than those in Nigerians, yet the quinidine-induced QTc increase was greater in white British subjects than in Nigerians (Olatunde and Price Evans 1982).…”
Section: Resultsmentioning
confidence: 98%